Strategi Pembelajaran Dalam Optimalisasi Kecerdasan Musikal Anak Di TK Dharma Bahagia Samarinda - Budi Rahardjo; Naning Sutriah; Fachrul Rozie (Universitas Pendidikan Indonesia Kampus Serang, 2019)
This study aimed to reveal the strategies implementation, supporting and challenging factors in singing learning strategies in Dharma Bahagia kindergarten school in optimizing children's musical intelligence. This research used a qualitative approach with case studies type. The research subjects included the school principal, teacher, trainer and 8 children aged 5-6 years. Data collection techniques used were in-depth interviews, observation, and documentation with interactive models of data analysis. The results revealed that the strategy used was a demonstration strategy when the teacher taught children directly the steps to memorize lyrics and direct teaching guided by the teacher in memorizing songs and tones. The trainer role was limited to the training process outside the classroom. Some challenging factors that arised are the teachers’ lack of preparation and the dependence of the trainer's schedule and the lack of learning media facilities to support singing activities. It causes an unconducive learning atmosphere and lack of song lyrics memorization. The supporting factors found included high children enthusiasm in participating in singing activities, the teachers’ activeness in directing children, and that involving music activities and a conducive space to practice singing activities. The results concluded that a demonstration strategy and direct teaching can optimize musical intelligence in classroom learning.